Pengaruh Return on Equity, Current Ratio, Size Company dan Debt to Equity Ratio Terhadap Nilai Perusahaan - Ika Listyawati; Ida Kristiana (Universitas Muhammadiyah Semarang, 2020)
Firm value is a factor that investors consider in making investment decisions. This study examines the effect of profitability, liquidity, company size and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2014 - 2018.The sample used in this study consists of 34 manufacturing companies listed on the Indonesia Stock Exchange in 2014. 2014 - 2018. The sample was taken by using purposive sampling method.The variables used are Price Book Value (PBV), Return on Equity (ROE), Current Ratio (CR), Total Asset (Size) and Debt to Equity Ratio (DER). The population is all manufacturing companies listed on the Indonesia Stock Exchange as many as 34 companies during 2014-2018. The results showed that Return on Equity (ROE) had a positive and significant effect on Price Book Value (PBV), Current Ratio (CR) had a positive and significant effect on Price Book Value (PBV), Firm Size had a positive and significant effect on Price Book Value ( PBV), Dept on Equity Ratio (DER) have a negative and significant effect on Price Book Value (PBV).